One Pot Green Synthesis and Structural Characterisation of Bio-Silver Nanoparticles Using Prunus Persica L.: Life Sciences-Biochemistry for better Diagnosis and Therapy - S.Shamina; Dr.S.P.Suriyaraj; V.Senjiskhan (International Journal of Life Science and Pharma Research, 2022)
The Plant mediated green synthesis of nanoparticles has attracted more attention among the researchers due to their physicochemical and biological properties and their immense applications in environmental, biomedical, agriculture, textile, and energy storage. The biosynthesis of nanoparticles using plants provides more advantages such as easy operation, eco-friendly, utilization of non-hazardous chemicals, less temperature or energy usage, etc. when compared to physical and chemical synthesis methods. In the present study, we propose aqueous extracts from the endemic-medicinal fruit Prunus persica L. as an efficient bioproduct for the green synthesis of silver - nanoparticles (AgNPs). The biosynthesized AgNPs were characterized using UV-Visible spectroscopy, Fourier transforms Infrared spectroscopy (FTIR) High-Resolution Transmission electron microscopy (HR-TEM), Scanning electron microscopy, Atomic Force Microscopy (AFM), and X-ray diffractometer (XRD). HR-TEM gives the formation of monodispersed spherical shape with a mean diameter of 12.6 ± 3.8 nm. The SAED pattern of the nanoparticles showed that the particles were highly crystalline in nature. The purity of the synthesized AgNPs samples was studied by EDS and confirmed the presence of Ag elements corresponding to TEM images. The 2D and 3D structure images of the nanoparticle were studied and the average particle size calculation has been performed using NOVA-TX software in AFM. X-ray diffraction analysis showed that the particles were crystalline in nature with face - centered cubic structure. The antimicrobial efficacy was evaluated using the resazurin assay against both Escherichia coli and Bacillus subtilis bacteria. The antimicrobial assay of the silver nanoparticles showed higher activity against Bacillus subtilis than Escherichia coli. Results confirmed this protocol as rapid, simple, eco-friendly and alternative to conventional physical, and chemical methods.